Petroleum Exploitation or Human Exploitation? An Overview of Niger Delta Oil Producing Communities in Nigeria (2009)
This paper examined the impact of petroleum exploitation on the environment of the Niger Delta oil producing communities in Nigeria. This is in furtherance of the understanding that human beings are at the centre of concerns for sustainable development. The paper observed that there was need for the adoption of measures that would provide a reasonable degree of protection of ecological and human environment from the activities of the oil industry in Nigeria.